Differentiation of potato samples using a modified High Identity Traits (HITS) method is greater with trained panels than untrained - Ciccone, Melissa (Kansas State University, 2019)
Descriptive Sensory Analysis uses a highly trained panel of assessors to develop detailed profiles of products based on their appearance, aroma, flavor, and/or texture. These comprehensive product profiles can be important to product development and quality control processes, but long lists of attributes may not be necessary for preliminary research and development decision-making. An alternative method previously was developed to create simplified product profiles centered on no more than five High Identity Traits (HITS), or characteristics that are most important to the identity of a sample. This research examined two different applications of a modified HITS method. The goal of the first study was to determine which of five cooking methods best facilitates the differentiation of potato varieties by descriptive analysis. Five potato varieties were each prepared using boiling, mashing, baking, deep frying, and air frying methods. Six, highly trained panelists evaluated the aroma, flavor, and texture of each sample to develop a list of up to five HITS. Additionally, panelists scored each sample for Degree of Difference (DOD) from a control. Based on the HITS profiles and DOD scores, mashing, baking, and air frying methods were all effective in differentiating the samples, while frying and boiling methods introduced too much variation and are not recommended for future descriptive studies. The objective of the second study was to find out if an untrained consumer panel could provide similar sensory profiles to a highly trained panel using the modified HITS method. Based on the results from the first study, an untrained panel of six consumers evaluated five potato varieties cooked by mashing, baking, and air frying. The consumers developed HITS profiles and rated each sample for DOD. The results of this panel were compared to the mashed, baked, and air fried results from the first study. The consumer panel was able to identify differences and some of the same traits as the trained assessors, but did not develop similar sensory profiles overall. While the highly trained assessors were able to identify complex aroma and flavor traits, the consumers focused mainly on texture, which prevented them from finding more subtle product differences. The results of these studies show that a highly trained descriptive panel can use HITS profiles to differentiate products, which can help cut time and costs when making preliminary decision regarding sensory characteristics.
Keywords: Potatoes; Sensory; High identity traits; Trained versus untrained; Cooking method